Distributions of Stellar Systems Using Mathematica With Applications to Cataclysmic Variables and Planetary Nebulae - Sharaf, Mohammed (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, Meisel's(2013) algorithm for the distribution of galaxies using Mathematica was used for the distributions of Cataclysmic Variables(CV) and Planetary Nebulae(PNe) . Data manipulationsare illustratedgenerally, through the Internet data sources and the implementation for Mathematica usage. The distributions are displayed in two dimensions ,the galactic longitude andgalactic latitude. The distributions of both CVs and the PNe are symmetric about the galactic plane, with high condensation of PNe towards the plane which supports the known fact that PNe are young. On the other hand ,the remarkable condensation the remarkable condensation at high galactic latitudes of CVs indicates that these objects are old.